IMPACT OF SOWING DATES ON THE YIELD EFFICIENCY OF UPLAND RICE CULTIVARS - Meirelles, Flávia Constantino [UNESP]; Arf, Orivaldo [UNESP]; Garcia, Nayara Fernanda Siviero [UNESP]; Takasu, Anderson Teruo [UNESP]; Buzo, Fernando de Souza [UNESP]; Portugal, José Roberto [UNESP]; Portugal, Amanda Ribeiro Peres [UNESP] (PPUFU - Portal de Periódicos da Universidade Federal de Uberlândia, 2022)
The choice of cultivars adapted to different regions and the determination of the best sowing dates are indispensable tools for crop development. This allows the installation of the crop in times favorable to its development, as well as cultivars that manage to reach their maximum yield potential. The objective of this study was to determine the best sowing dates and the cultivars that can adapt to the low-altitude Cerrado region and have the best development and yield efficiency. The experiment was conducted on a typical clayey dystrophic Red Latosol soil. The experimental design was in randomized blocks in a factorial scheme, comprised by four sowing dates during the spring/summer season (October, November, December, and February) and in each sowing date there were eight upland rice cultivars (BRS Esmeralda, ANa 6005, ANa 5015, IPR 117, IAC 203, IAC 500, ANa 7211 and BRSGO Serra Dourada) with four replicates. Sowing in October and November benefited the aerial dry mass and the spikelets fertility however, sowing in November provided higher plant height, which caused lodging in plants. Sowing in December caused the incidence of scald, mainly affecting the cultivar ANa 7211. For all cultivars, sowing in October favored the yield efficiency of upland rice in the low-altitude Cerrado, followed by sowing in November. The cultivars which demonstrated higher yield efficiency in the conditions of the region were BRS Esmeralda and ANa 5015.
Keywords: Cerrado; Global solar radiation; Oryza sativa L; Sprinkler irrigation